The Normative Order of International Politics: Critique and Legitimacy - Thorsten Thiel (Navigating Normative Orders: Interdisciplinary Perspectives, 2020)
The article discusses the politicisation of international politics and its effects on the legitimacy of international institutions. It is argued that a more complex understanding of the interplay of institutional and non-institutional practices of resistance is needed and that one has to draw from theories of international relations as well as from approaches from democratic heory to better understand the developments and its effects on the legitimacy of international institutions. The article proceeds by, first, reconstructing how research in IR has responded to the emergence of civil society critique, focusing in particular on the debate about inclusion through liberal governance mechanisms and the discussion of the regulatory power of counter-hegemonic actors in critical theories; it then turns to democratic theoretical approaches, in which the concept of “opposition” becomes a cipher for legitimate critique, yet the value of opposition and its form is determined very differently in different lines of thought. Finally, it is shown that the debate on the politicisation of international relations would particularly benefit from a republican understanding of politics, since the analytical focus and normative impetus lies in the relation between the visibly controversial nature of order and the creation of sites for opinion formation in civil society.
Keywords: 330; international political theory; dissidence; opposition; republicanism